Sociolinguistics: Indonesian – English Code Mixing Used by Sport Commentators in Indonesian Football League - Ida Bagus Baskara Putra Subali; I Dewa Ayu Devi Santika Maharani (CV Wahana Publikasi, 2023)
Code is another term for language in sociolinguistics, and many bilingual people use different codes when having conversations with others. The phenomenon of using different codes nowadays is known as code-mixing. This study aims to find out the function of code mixing used by the football presenters’ dialogues in the Indonesian Football League, especially during the match between Bali United FC and Persija Jakarta. The methodology of this research is a descriptive qualitative method, and it is used to find out the functions of using code mixing during a football match. In the analysis, Hoffman’s theory (1991) is used. It is found 134 data that classified into seven different functions, such as talking about a particular topic with the amount of 86.5 %, which became the most dominant function, followed by interjection with 4.5 %, similarly, with the function of quoting somebody else with 4.5 % of data, the third position is placed by repetition used for clarification with only 1.5 % of utterances, same with expressing group identity as amount 1.5 %, and for the lowest functions are filled by being emphatic about something with only 0.7 % and also clarifying the speech content for interlocutor with 0.7 % as well. This result is strengthened by the intention of the football presenters to analyze the football game with a different language because they want to talk about specific terms that are used to describe the situation that occurred during the match.